Studies on ecology of phytoplankton from Pichavaram mangroves, South East Coast of India - V. Ashok Prabu, T. Nedumaran (Journal of Phytology, 2009)
The spatial and seasonal distribution of phytoplankton species and their abundance to hydrographical parameters were studied during April 2000 and March 2001 from two stations of Pichavaram mangroves located in south east coast of India, (Lat. 11Ã‚Â°27Ã¢â‚¬â„¢N: Long 79Ã‚Â°47E).Ã‚Â During the study 91 species of phytoplankton were recorded which belongs to different groups viz. Diatoms (73), Dinoflagellates (17) and Slicoflagellates (1). Species such as Coscinodiscus centralis, Pleurosigma elongatum, Thalassionema nitzschioides, Skeletonema costatum Triceratium favus, Odentella sinensis, Navicula longa and Ceratium furca Constituted bulk of the population density.Ã‚Â More number of species was recorded at station 1 and the production of phytoplankton was very high during summer season. The temperature, salinity, pH and dissolved oxygen examined fairly stable during the study period except monsoon. During the summer season nutrients level was low as well as the phytoplankton density was very high.